Hot-wire anemometer based on fiber Bragg grating coated with carbon conductive paint - SHAHRIL, MUHAMMAD RIDZWAN; Yusof, Muhammad Khudhori; FATIHAH AZAHAN, SITI NURUL; MOHD FARID, SABRINA; KOK SING, LIM; Ahmad, Harith; Zulkifli, Mohd Zamani (National Institute of Optoelectronics, 2025)
Hot-wire anemometers are sensors used to measure wind speed via the principle of thermal equilibrium. They are attributed to the issue of probe contamination, requiring regular maintenance, causing inaccurate measurements. A hot-wire anemometer based on FBG coated with carbon conductive paint is proposed. 2 mm coating is applied on the FBG grating region using brushing method. The sensitivity of the proposed anemometer is 0.0410 nm / (m/s) in the temperature range of 60 °C to 150 °C, at wind speeds of 0 m/s, 4.55 m/s , 4.86 m/s and 5.02 m/s. The FBG is proven to possess increased sensitivity towards temperature, improving its thermal anemometry capabilities.